A permacultura como instrumento de sustentabilidade na comunidade rural Chã de Jardim, Areia - PB - Dantas, Bianca Rufino Nascimento (2017)
Sustainability carries theories and ideals that seek to solve problems before the time of crisis. Permaculture, is already a summary of traditional knowledge allied to scientific knowledge, which seeks to be guided by the theory of sustainability to bring efficiency and self-management to society; bringing these solutions to practical use. From the use of alternative tools for housing, energy, tourism, agriculture, education, health, communication and all areas covering the demand of human life on earth. Their multi / transdisciplinary perspective reflected their goal of creating autonomous, aware, and more human. The Chã de Jardim rural community, located in the Paraíba marsh in the city of Areia, has attracted the attention of visitors, as residents have developed a a strategy of community-based tourism where they are the protagonists, creating and self-managing their resources and tourist practices in support of local sustainability; and this has been contributing in the recovery and recovery of their customs. The approach performed by this tourism is based on permaculture practices. But beyond that point, other social demands have a strong community base that marks the community and confirms the presence of permaculture resources. Giving from the formation of the affective bonds and the sense of living in community, from networks and mutual support. This research sought to answer the question: "Can permaculture contribute to the sustainability of the rural community Chã de Jardim, Areia - PB?". To this end, the theoretical references studied Permaculture, sustainability and community based tourism in rural areas. Qualitative interviews were conducted with members of the community to investigate the permaculture elements present, problematic in general, as well as perceptions about the place and about tourism. And it was used as a method of analysis of the results, the flower of Permaculture based on an evaluation of the sustainability criteria. At the end we expose the problems identified in the place by the informants, to make contributions of permaculture. We realized that several existing permaculture elements contribute to the sustainability of the rural Chã de Jardim community. There are practices that are growing and strengthening gradually, and that this growth is the result of an awareness of the community coming from a struggle for permanence in the countryside. In addition, even decreasing practices can be reconfigured and become a creative potential of change, because they are already part of their customs, and then it would only require local and / or external initiative at the continuation of the same. However, the largest result of the research was to realize that the community has become to research, an ' under construction ' example of permaculture in practice, and it is from these examples that we can improve this 'science' itself. This sense of community and between those involved is learned by the simplicity in which they are transmitted and by coexistence in the face of difficulties. And it is from this sense of community and conscience that the efficient use of the resources of the environment will have effectiveness and empowerment on the part of the community.